Subsidiary classification, and configuration with a developmental context : evidence from foreign multinational enterprises in New Zealand : a thesis presented in partial fulfilment of the requirements for the degree of Doctor Philosophy in Strategic Management at Massey University, New Zealand - Raziq, Muhammad Mustafa (Massey University, 2015)
Research has produced a range of subsidiary classifications indicating various ways in which subsidiaries can be distinguished. There are, however, still concerns that many of the critical contingencies remain unexplored. It is, for example, argued that the existing subsidiary types are either multinational enterprise (MNE) strategy-based or process-based, rather than based on the subsidiary’s own strategy. The frameworks are: two-dimensional (Enright & Subramanian, 2007; Morschett, Schramm-Klein, & Zentes, 2015); lack theoretical basis; and, their dimensions are arbitrary (Schmid, 2004; Schmid, Dzedek, & Lehrer, 2014). They are also disconnected to the previous frameworks (Hoffman, 1994). MNE management structure is one such contingency. Subsidiary studies mostly focus on the corporate headquarters (CHQ) as the subsidiary developmental driver, but ignore the varying developmental influences. Namely, the structures (i.e., lateral or formal) placed on subsidiaries. Most of the ignored contingencies are contextual (Enright & Subramanian, 2007; Meyer, Mudambi, & Narula, 2011). Little is known about how various subsidiaries configure with these contexts. Putting subsidiary development to the fore, these issues are integrated and two research objectives are set. One issue concerns developing a subsidiary classification, and the other concerns subsidiary and context configuration. This thesis’s empirical context is foreign subsidiaries in New Zealand. Data from 429 subsidiaries are obtained. Cluster analysis and variance analysis are the key techniques used. Grounded in the resource-based view, resource dependence theory, and network theory, an overarching subsidiary classification framework is produced. The framework follows a contingency approach and draws on critical dimensions from the various subsidiary literature streams. From this framework a new three-part subsidiary developmental classification (entrepreneurial, constrained autonomous, constrained) is produced. By applying a configurational approach, various linkages are explored between the three subsidiary types and their developmental contexts. A number of developmental contingencies are identified; such as MNE management structures, expatriation, internationalisation motives, and internal isolation. Key findings include the lateral structure as the one under which subsidiaries develop the most, and the CHQ, the least. Individual developmental paths for the three subsidiary types are proposed. Theoretical implications are subsequently made, mainly identifying factors through which subsidiaries can develop resources and form internal resource dependencies. The novelty of the findings is discussed and subsidiary management and public policy implications are made. Keywords: MNE Strategy, Subsidiary Strategy, Subsidiary Development, Subsidiary Classification, Developmental Context, MNE Management Structure.
Keywords: Subsidiary corporations; International business enterprises; MNE strategy; Subsidiary strategy; Subsidiary development; Subsidiary classification; Developmental context; MNE management structure